IMPORTANCE AND PERFORMANCE ANALYSIS OF HOTEL SELECTION FACTORS AT FOUR POINTS BY SHERATON MANADO - Dewantara, I Made J.D.; Arie, Fitty V. (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2019)
Abstract: Competition in the hotel industry is getting tougher, Hotel’s management are required to know what travelers are looking at hotels, how they take their decision for a selection of hotels. This research aims to analyze which selection factors are considered as important and what is the actual performance of these particular hotel selection factors at Four Points by Sheraton Manado. This research uses Importance and Performance Analysis in order to analyze the data. 100 guests who stayed there were surveyed as the respondents. The result shows there are employee service quality located in quadrant I it means this factor has a high importance and low performance. Security and rooms and receptionist are located in quadrant II means that these factors has both high importance and performance. Food and recreations located in quadrant III which means this factor are both have low importance and performance. Value located in quadrant IV it means this factor is considered less important but the performance is good. Based on the result there are recommendations for Four Points by Sheraton Manado to keep maintain those factors that have high importance and high performance and improve those factors that have low in performance.Keywords: hotel selection factors, consumer preference, service quality, customer satisfaction, importance and performance analysis.